Mechanisms of platelet activation in cancer-associated thrombosis: a focus on myeloproliferative neoplasms - Bekendam, Roelof H.; Ravid, Katya (Frontiers in Cell and Developmental Biology, 2023)
Platelets are anucleate blood cells that play key roles in thrombosis and hemostasis. Platelets are also effector cells in malignancy and are known to home into the microenvironment of cancers. As such, these cells provide central links between the hemostatic system, inflammation and cancer progression. Activation of platelets by cancers has been postulated to contribute to metastasis and progression of local tumor invasion. Similarly, cancer-activated platelets can increase the risk of development of both arterial and venous thrombosis; a major contributor to cancer-associated morbidity. Platelet granules secretion within the tumor environment or the plasma provide a rich source of potential biomarkers for prediction of thrombotic risk or tumor progression. In the case of myeloproliferative neoplasms (MPNs), which are characterized by clonal expansion of myeloid precursors and abnormal function and number of erythrocytes, leukocytes and platelets, patients suffer from thrombotic and hemorrhagic complications. The mechanisms driving this are likely multifactorial but remain poorly understood. Several mouse models developed to recapitulate MPN phenotype with one of the driving mutations, in JAK2 (JAK2V617F) or in calreticulin (CALR) or myeloproliferative leukemia virus oncogene receptor (MPL), have been studied for their thrombotic phenotype. Variability and discrepancies were identified within different disease models of MPN, emphasizing the complexity of increased risk of clotting and bleeding in these pathologies. Here, we review recent literature on the role of platelets in cancer-associated arterial and venous thrombosis and use MPN as case study to illustrate recent advances in experimental models of thrombosis in a malignant phenotype. We address major mechanisms of tumor-platelet communication leading to thrombosis and focus on the role of altered platelets in promoting thrombosis in MPN experimental models and patients with MPN. Recent identification of platelet-derived biomarkers of MPN-associated thrombosis is also reviewed, with potential therapeutic implications.